Herbage Production During Drought in Silvopastoral Systems on a Rocky Rangeland in Arid Zone of India - Singh, K C; Rao, A S (Annals of Arid Zone, 2016)
A study on herbage production in silvopastoral systems on rocky rangeland, Bhopalgarh, conducted during drought years 1999 and 2000 with five tree and two shrub species at 14 and 15 year of age revealed that average air dried herbage yield in the inter spaces (10 x 4 m) of different silvopastures was lowest with Dichroslachys Illi/ans (620 kg ha·l ) compared to other silvopastoral systems as well as pasture without trees except Acacia lorlilis (804 kg ha-1 ). Acacia lorlilis showed maximum survival (96.66%) and growth in height (4.86 m), collar diameter (16.3 em), dbh (11.03 em) and canopy diameter (6.63 m). The survival percentage of Acacia senegal and D. nwans was 81.66 and 78.33%, respectively, which showed that 3 MPTS viz., A. to rlilis , Acacia senegal and D. nutans were found better establishing on rocky rangeland. Among these A. senegal was most suitable for long term silvopasture. Leaf fodder yield was maximum in D. mllans (8.89 kg tree·l) followed by Azadirachla indica (6.50 kg tree-I), A. torlilis (5.00 kg tree-I) and A. senegal (4.95 kg tree-I), while fuel wood yield was highest in A. lortilis (68.00 kg tree''). A comparison of weather parameters during good rainfall years with that of drought years (1999 and 2000) revealed that during drought years, the air temperatures were higher by 0.8°C, relative humidity was lower by 4% and duration of bright sunshine hours increased by 0.3 hr day"l resulting in higher evaporation rates by 1.5 mm day"l. The study on impact of drought showed that the decline in herbage production was highest in D. nulans (65%) followed by Azadirachla indica (57%), A. senegal (54%), Hardwarckia binata (52%), Colophosperlllll/ll mopane (51 %), A. lorlilis (49%), Albizia lebbek (48%) and in sole grass without tree (47%). Key words: Silvopasture, herbage production, droughtrocky rangelands.